The study movement games in physical education class with primary school students - Gabriel, Marconi Roberto; Andrei, Liviu Vasile (Arena-Journal of Physical Activities, 2023)
Movement games used both with technical elements from handball in physical education lessons with primary school children will manage to optimize the instructional-educational process and consequently will favor the faster and quality acquisition of skills and motor skills, the development of morpho- functional and basic motor skills of students. The purpose of the research it is the optimization of the physical education teaching process by using movement games with technical handball elements in physical education lessons with primary school students. The objective is to argue and experimentally verify the effectiveness of the methodology regarding the use of movement games with technical handball elements within physical education lessons with primary school students. The basic direction of the research was the learning of some elements and procedures from the game of handball through movement games, adapted to the psychomotor peculiarities of the age of students from the 4th grade (10-11 years). The independent variable, used in the experimental group, was the introduction, within the thematic planning, of handball elements in the form of movement games.